Plant cyanogenic glycosides: an overview - Dwi Hartanti; Arinda Nur Cahyani (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2020)
The cyanogenic glycosides have consisted of α-hydroxy nitrile aglycone and a sugar moiety that producing hydrogen cyanide (HCN) during the hydrolysis process. This HCN-producing property underlines the toxicity of the plants commonly associated with these compounds in humans and animals. However, new evidence shows that the toxicity of these compounds is lower than those theoretically caused by the equivalent released HCN. In order to provide a deeper understanding of cyanogenic glycosides, an overview of these compounds is given in this article. It covers the chemistry, distribution, biosynthesis, toxicity, determination, as well as extraction and isolation of the compounds.